Pengaruh Upah Kerja Terhadap Beban Kerja Pada Pekerja Usia 18 - 25 Tahun - Khaila Deska Nuvie; Nadira Ash Shabilla; Rismawati Nurraihani; Eka Devi Trisnawati; Riyani Rahayu; Saridawati (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
Wages or salaries are financial rewards that workers receive as compensation for their efforts in the production process. According to various sources, workload is defined as the number of activities or responsibilities that must be completed in a certain time. This research used a quantitative approach by distributing questionnaires to 31 respondents taken randomly via social media. The data obtained was analyzed using simple linear regression analysis to determine the relationship between work wages (variable X) and workload (variable Y). This research makes an important contribution to understanding the relationship between wages and workload among young workers. The practical implication of this research is the need to improve the wage system that is fairer and more balanced with workload to increase worker productivity and welfare. Apart from that, it is hoped that the results of this research can be used as consideration for policy makers in formulating better and fairer employment policies. Keywords: Wages, Workload